Prendre position: une approche sémantique des conflits publics - Lescano, Alfredo M. (Revista Conexão Letras, 2018)
This paper proposes that social conflicts have a relatively autonomous semantic structure. In this perspective, discourses that define positions, instead of communicating or persuading, work on installing, conserving or transforming discursive possibilities within a semantic space. The emergency of a discourse is always an intervention into the space of the speakable (to maintain it or to modify it). Among different kinds of positions that can be created, there are those which install a binomial zone of convergent / divergent speech, and those which build Reality, which excludes divergence. The proposal is developed within a more general discussion about the links between semantics and ideology.